PREVALENCE AND FACTORS INFLUENCING BIOFILM-PRODUCING BACTERIA ON THE TOOTHBRUSHES OF HEALTH SCIENCES UNDERGRADUATE STUDENTS: Biofilm Bacteria Growth on Toothbrushes Among Health Sciences Undergraduates - ABD MURAD, NUR AIN; ANDI TAKDIR ALAMSHAH, NURSALIHAH; AHMAD, NA'EL AWATEEF; AHMAD YUSOF, HANANI (International Journal of Allied Health Sciences, 2024)
Introduction: Biofilm is the formation of microorganisms that adhere to surfaces, producing a matrix that makes them resistant to harsh conditions such as antimicrobial therapies. This resistance can result in prolonged and challenging infection treatment. Common items like toothbrushes can harbour microbes that produce biofilm, thus contributing to adverse effects for the users. However, the factors that might interplay with the occurrence of biofilm on toothbrushes are scarce. Hence, this study aimed to understand the prevalence and potential causes of biofilm-producing bacterial contamination of toothbrushes among undergraduate students of a health sciences campus. Methodology: The study included 36 respondents, selected through convenience sampling. Each respondent completed a questionnaire that addressed demographic information, toothbrush characteristics, and oral hygiene practices. Their toothbrushes were tested by soaking the bristles in distilled water for 30 minutes, and then cultivating the water on Congo Red Agar plates. Results: Biofilm-producing bacteria were identified by the black and dry colony growth on the plates. Bacterial growth was observed on all toothbrushes, with five identified as biofilm producers. The study found no significant association (p>0.05) between toothbrush characteristics or oral hygiene practices and the presence of biofilm-producing bacteria on the toothbrushes. Conclusion: The findings suggest that toothbrushes can harbour bacterial growth, indicating the need for further research to understand the potential health implications.